Clinical illness and outcomes in Nigerian children with late-appearing anaemia after artemisinin-based combination treatments of uncomplicated falciparum malaria. Issue 1 (December 2016) - Sowunmi, Akintunde; Akano, Kazeem; Ayede, Adejumoke; Ntadom, Godwin; Aderoyeje, Temitope; Adewoye, Elsie; Fatunmbi, Bayo
Abstract Background Late-appearing anaemia (LAA) following treatment with artemisinins for severe malaria has been reported and well described, but there are limited clinical and parasitological data on LAA in African children with uncomplicated falciparum malaria following oral artemisinin-based combination therapies (ACTs). Methods This was an open label study with the main objectives of evaluating the clinical features, the risk factors for, the temporal changes in haematocrit and the outcomes of a LAA in malarious children treated with artesunate-amodiaquine (AA), artemether-lumefantrine (AL) or dihydroartemisinin-piperaquine (DHP). The diagnosis of LAA was made using the criteria: clearance of parasitaemia, fever and other symptoms within 1 week of commencing treatment; adequate clinical and parasitological response at 4–6 weeks after treatment began; haematocrit ≥30 % 1 and/or 2 weeks after treatment began; and haematocrit <30 %, parasite negativity by microscopy and polymerase chain reaction and absence of concomitant illness 3–6 weeks after treatment began. Results LAA occurred in 84 of 609 children, was mild, moderate or severe in 77, 6 or 1 child, respectively and was relatively asymptomatic. Mean time elapsing from commencement of treatment to LAA was 27.1 days (95 % CI 25.3–28.9). In a multivariate analysis, an age <3 years (adjusted odd ratio [AOR] = 2.6, 95 % CI 1.3–5.2, P  = 0.005), fever 1 day after treatment began (AOR = 3.8, 95 % CI 1.8–8.2, P  < 0.0001), haematocrit <25 % at presentation (AOR = 2.2, 95 % CI 1.3–3.7, P  = 0.003), haematocrit <30 % 1 day after treatment began (AOR = 2.1, 95 % CI 1.0–4.3, P  = 0.04), parasite reduction ratio >104 2 days after treatment began (AOR = 2.1, 95 % CI 1.1–3.9, P  = 0.03) and spleen enlargement at presentation (AOR = 2.0, 95 % CI 1.1–3.9, P  < 0.0001) were independent predictors of LAA. During 6 weeks of follow-up, uneventful recovery from anaemia occurred in 56 children [mean recovery time of 11.8 days (95 % CI 10.3–13.3)]. The only independent predictor of failure of recovery was LAA occurring 4 weeks after starting treatment (AOR = 7.5, 95 % CI 2.5–22.9, P  < 0.0001). Conclusion A relatively asymptomatic LAA with uneventful recovery can occur in young malarious children following ACTs. Its occurrence may have implications for case and community management of anaemia and for anaemia control efforts in sub–Saharan Africa where ACTs have become first-line antimalarials. Trials registration Pan African Clinical Trial Registry PACTR201508001188143, 3 July 2015; PACTR201510001189370, 3 July 2015; PACTR201508001191898, 7 July 2015 and PACTR201508001193368, 8 July 2015http://www.pactr.org .